YouTube Streaming Performance Over Wi-Fi: A Resolution-Based Analysis - Haries Anom Susetyo Aji Nugroho; Sonhaji; Andika Chandra Prasetyo (LPPM Universitas Islam 45 Bekasi, 2025)
The quality of YouTube video streaming services affects the learning process through video streaming. With poor video service quality, it will disrupt the process of obtaining information. Therefore, there is a need for good video service quality following existing service quality standards on the internet network, according to ITU. Streaming video on YouTube consists of several resolutions. The higher the video resolution, the better the video quality but inversely proportional to the greater the internet bandwidth required. This research tries to compare the quality of YouTube video streaming services at 480p and 720p resolutions to find out if there is a significant difference between the two resolutions of video streaming services. The results obtained from this study are to determine whether or not there is a significant difference between 480p and 720p video streaming services as a consideration in determining network service policies. The method used in this research is to observe data collection directly on WiFi spread in the university environment and the data is processed to get quality of service value at 480p and 720p video resolution. Then the results of the data processing are analyzed again with statistical tests to obtain information from the comparison of the two streaming video resolutions in terms of throughput, jitter, delay, and packet loss. The results of the research show that there are no significant differences in delay, jitter, throughput, and packet loss on YouTube video streaming services at 480p and 720p resolutions.